ملامح الحداثة في شعر يوسف الخال - جابر, يوسف حامد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
تمثل الحداثة الشعرية حركة نامية تهدف إلى التجديد المستمر لبنية الشعر ودفعها إلى الأمام، من خلال التطلع والبحث والكشف وتجاوز القديم، في محاولة لجعل الشعر يضارع الحياة في تطورها وتبدل أشكالها. وإذا كان الشاعر يوسف الخال يمثل أحد أبرز وجوه حركة الحداثة في الشعر العربي الحديث من خلال وعيه بأهمية تحديث الشعر، وضرورة مواكبته للحياة، فإن هذا البحث يسعى للوقوف على أبرز تجليات الحداثة في شعره، ويحاول وصفها، وإضاءة مرتكزاتها. Poetic modernism represents a developing move that tends to achieve constant renewal to the structure of poetry, as well as, keep it abreast via aspiration, research, investigation and marginalizing the archaic, in an attempt to make poetry match the changes and improvements of everyday life. However, if the poet Yusuf al-Khal represents one of the most famous figures of modernism in the contemporary Arabic poetry, as it is apparent in his intelligibility of the significant need to modernize poetry , and harmonize as its essentialities, then this piece of research endeavours to discuss the most obvious aspects of modernism in his poetry, describing and highlighting its core basics .